2010
DOI: 10.1007/s00125-010-1681-4
|View full text |Cite
|
Sign up to set email alerts
|

The Framingham and UK Prospective Diabetes Study (UKPDS) risk equations do not reliably estimate the probability of cardiovascular events in a large ethnically diverse sample of patients with diabetes: the Action in Diabetes and Vascular Disease: Preterax and Diamicron-MR Controlled Evaluation (ADVANCE) Study

Abstract: Aims/hypothesis Available multivariable equations for cardiovascular risk assessment in people with diabetes have been derived either from the general population or from populations with diabetes. Their utility and comparative performance in a contemporary group of patients with type 2 diabetes are not well established. Diabetologia (2010) 53:821-831 DOI 10.1007/s00125-010-1681 Framingham and the UKPDS risk equations in 7,502 individuals with type 2 diabetes without prior known CVD at their enrolment in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 36 publications
9
91
0
Order By: Relevance
“…The ADDITION cohort included people with screen-detected diabetes. Other research 125,133 has shown that the UKPDS-OM tends to overestimate absolute CVD risk, a finding replicated in our own investigation of the suitability of the UKPDS-OM to extrapolate ADDITION study data. 96 Furthermore, the utility decrements for MI and stroke derived from the ADDITION study were smaller than those in the UKPDS, a finding that is consistent with contemporary patients receiving better care and hence reporting higher quality of life.…”
Section: Strengths and Limitationssupporting
confidence: 80%
“…The ADDITION cohort included people with screen-detected diabetes. Other research 125,133 has shown that the UKPDS-OM tends to overestimate absolute CVD risk, a finding replicated in our own investigation of the suitability of the UKPDS-OM to extrapolate ADDITION study data. 96 Furthermore, the utility decrements for MI and stroke derived from the ADDITION study were smaller than those in the UKPDS, a finding that is consistent with contemporary patients receiving better care and hence reporting higher quality of life.…”
Section: Strengths and Limitationssupporting
confidence: 80%
“…There were relatively few events observed at HbA 1c levels less than 6.5% making the estimates of the associations at these HbA 1c levels less precise than at higher levels. Moreover, the selective nature of trial participants and the potential influence of randomised treatments may affect the generalisability of the findings, although the ADVANCE participants are fairly typical of current populations with type 2 diabetes managed in the community [19]. Finally, despite extensive multiple variable adjustment, these analyses may be unable to completely eliminate the effects of residual confounding attributable to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were largely conducted in Europe or the USA, and almost exclusively included Caucasian patients, though the largest study was a multi-ethnic study, including populations from different countries [16]. The proportion of Caucasians in studies varies between 30 and 100%.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%